Synthesis and Helical Structures of Poly(ω‐alkynamide)s Having Chiral Side Chains: Effect of Solvent on Their Screw‐Sense Inversion. Issue 46 (26th September 2014) - Suzuki, Yuji; Miyagi, Yu; Shiotsuki, Masashi; Inai, Yoshihito; Masuda, Toshio; Sanda, Fumio
Abstract New ω‐alkynamides, (S)‐HCCCH2CONHCH2CH(CH3)CH2CH3 (1) and (S)‐HCCCH2CH2CONHCH(CH3)CH2CH2CH2CH2CH3 (2) were synthesized and polymerized with a rhodium catalyst in CHCl3 to obtain cis‐stereoregular poly(ω‐alkynamide)s (poly(1) and poly(2)). Polarimetric, CD, and IR spectroscopic studies revealed that in solution the polymers adopted predominantly one‐handed helical structures stabilized by intramolecular hydrogen bonds between the pendent amide groups. This behavior was similar to that of the corresponding poly(N‐alkynylamide) counterparts (poly(3) and poly(4)) reported previously, whereas the helical senses were opposite to each other. The helical structures of the poly(ω‐alkynamide)s were stable upon heating similar to those of the poly(N‐alkynylamide)s, but the solvent response was completely different. An increase in MeOH content in CHCl3/MeOH resulted in inversion of the predominant screw‐sense for poly(1) and poly(2). Conversely, poly(3) was transformed into a random coil, and poly(4) maintained the predominant screw‐sense irrespective of MeOH content. The solvent dependence of predominant screw‐sense for poly(1) and poly(2) was reasonably explained by molecular orbital studies using the conductor‐like screening model (COSMO).